Teacher Education for Critical and Reflexive Interculturality - Dervin, Fred.; Jacobsson, Andreas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
At a time where intercultural dialogue appears to be in crisis, books such as this one are needed now more than ever before. It is an engaging and bold read from start to finish and a work vitally needed for those involved in teacher education and training around the world. The authors yield valuable and new insights into the complex field of interculturality. Professor Fanhua Meng, Capital Normal University, China The notion of interculturality is used, and at times misused and abused, in education and research. In Dervin and Jacobsson s book, with much needed boldness, we are called upon and inspired to be more critical and reflexive with this polysemic notion. Many of us in education have been hoping to get their hands on this excellent book. Professor Emerita Marie-José Barbot, University of Lille, France This book reviews and analyses the importance of interculturality in teacher education. Although some principles might be common across countries, there is no global agreement on the meanings of interculturality. Unlike most books on the topic, it is argued that educators should be critical of the notion and of the problematic influence it can have on students if used loosely. The authors provide an up-to-date review of the different meanings, concepts and methods used to define interculturality in teacher education. In doing so, they offer useful frameworks and strategies to address problems when teaching it. Including practical strategies as well as theoretical analysis, this book will be of use to teacher educators, student teachers and teachers to unthink and reformulate the way they engage with interculturality. Fred Dervin is Professor of Multicultural Education at the University of Helsinki, Finland. He also holds distinguished professorships in Australia, Canada, China, Luxembourg, Malaysia and Sweden. Dervin specialises in intercultural education, the sociology of multiculturalism and academic mobility. Andreas Jacobsson is Senior Lecturer in Intercultural Studies at Karlstad University, Sweden. His research is primarily focused on intercultural communication education, interculturality and early childhood education, intercultural film and media, intercultural epistemology and philosophy.
Chapter 1. Introduction: setting the stage -- Chapter 2.: Why use the word interculturality and not something else? What are the meanings of interculturality today? -- Chapter 3: Why does it really matter? What is interculturality all about in education? What are its goals? -- Chapter 4: What should teachers know about the idea of interculturality? -- Chapter 5: What should/could teachers learn to do with interculturality? -- Chapter 6: What concepts to use? -- Chapter 7: Step 1: Interculturality from within -- Chapter 8: Step 2: Interculturality and imaginaries -- Chapter 9: Step 3: Interculturality and language -- Chapter 10: Good practice 1: Using textbooks to explore interculturality -- Chapter 11: Good practice 2: The media as an educational resource to rethink interculturality -- Chapter 12: Good practice 3: Fiction and art as a support to develop a sense of interculturality -- Chapter 13. Conclusion.
Keywords: Teachers Training of; 9; Comparative education; Education Philosophy.; Learning, Psychology of; Schools; Teaching and Teacher Education; International and Comparative Education; Philosophy of Education; Instructional Psychology; Educational Philosophy; School and Schooling